Using instability to reconfigure smart structures in a spring-mass model. (July 2017) - Zhang, Jiaying; McInnes, Colin R.
Graphical abstract: Highlights: A smart structure model is developed as a spring-mass model based on nonlinearity to investigate the reconfiguration. In this paper a subset of unstable configurations of a smart structure model will be used to develop energy-efficient schemes to reconfigure the structure. It is proposed that transitions between such equal-energy unstable (but actively controlled) equilibria in principle require zero net energy input, compared to transitions between stable equilibria which require the input and then dissipation of energy. Dissipation is then added to be more representative of a practical structure. Then, a range of strategies are then used to reconfigure the smart structure using heteroclinic connections with different approaches to handle the dissipation terms. Abstract: Multistable phenomenon have long been used in mechanism design. In this paper a subset of unstable configurations of a smart structure model will be used to develop energy-efficient schemes to reconfigure the structure. This new concept for reconfiguration uses heteroclinic connections to transition the structure between different unstable equal-energy states. In an ideal structure model zero net energy input is required for the reconfiguration, compared to transitions between stable equilibria across a potential barrier. A simple smart structure model is firstly used to identify sets of equal-energy unstable configurations using dynamical systems theory. Dissipation is then added to be more representative of a practical structure. A range of strategies are then used to reconfigure the smart structure using heteroclinic connections with different approaches to handle dissipation.